Nietzschean types in The Brothers Karamazov : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University, New Zealand - Durkin, Patrick (Massey University, 2019)
Nietzsche and Dostoevsky were contemporaries, and Nietzsche especially was known to admire Dostoevsky’s work. Both authors were interested in the study of the basis for human morality, and the search for a redirection of human morality; one in which the problems they saw with the current understanding of acceptable behaviour according to laws, religion and might is right, could be melded in with their own beliefs and struggles with their own mortality and morality. Although Nietzsche’s collection of essays ​The Genealogy of Morals,​ (1887) was written 7 years after Dostoevsky’s ​The Brothers Karamazov ​(1880), it is interesting to note that the main character types that Nietzsche believed created hierarchies that developed and sustained the morality of his time, appear in the form of the main characters in ​The Brothers Karamazov​. This thesis will be looking at the ​The Brothers Karamazov​ through the different character ‘types’ and the resulting psychomachia of the three legitimate brothers, the older brothers Dmitri and Ivan, and especially that of Alyosha, the youngest brother. The thesis will focus on both elder brothers’ evolution of thought and action through the progress of the novel, and, importantly, on each brothers’ interactions with Alyosha and the turbulent state of mind they regularly leave their younger sibling in. The final chapter of the thesis will concentrate on Alyosha and his journey throughout the novel, from his parting of ways with Zosima to his talk with the young boys by the stone. This journey, I believe, will be the one that extracts the idea of Dostoevsky’s true morality seen in the novel.
Keywords: Dostoyevsky, Fyodor; Bratʹi︠a︡ Karamazovy; Criticism and interpretation; Nietzsche, Friedrich Wilhelm; Zur Genealogie der Moral; Ethics in literature; Religion in literature; 470505 Central and Eastern European literature (incl. Russian)